A rare species of Uropterygius (Anguilliformes, Muraenidae) found in the stomach content of a Yellow-lipped Sea Krait from Japan - Tashiro, Fumihito; Tabata, Runa; Nishizawa, Hideaki; Mitamura, Hidemichi (Check list (Luís Felipe Toledo), 2018)
A single muraenid specimen (genus Uropterygius), recovered from the stomach of a live Yellowlipped Sea Krait, Laticauda colubrina (Schneider, 1799), captured at Iriomote Island, Japan, was found to possess intermediate traits between 2 rare species, Uropterygius xenodontus McCosker & Smith, 1997 and Uropterygius golanii McCosker & Smith, 1997. The specimen is provisionally identified as U. xenodontus and is described below with its morphs, as an important addition to material of rare specimens of the genus in the western North Pacific.